2015
DOI: 10.1590/1413-78522015230401018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the 50-foot walk test and 30-sec chair stand test in total knee arthroplasty

Abstract: OBJECTIVE: To investigate the reliability of the 50-Foot Walk Test (50 FWT) and 30-second Chair Stand Test (30 CST) in patients who have undergone total knee arthroplasty (TKA). METHODS: The study was designed as a test-retest research. Thirty-three patients who would undergo bilateral TKA were recruited. The tests 30 CST and 50 FWT were performed twice on the same day with 5-minute intervals, respectively. Between the first and second tests, patients waited for an hour on sitting position in order to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…An average of two readings (in feet/second) was taken. The interclass correlation coefficient was 0.97 in previous studies (Dobson et al, 2013; Unver et al, 2015). …”
Section: Methodsmentioning
confidence: 54%
“…An average of two readings (in feet/second) was taken. The interclass correlation coefficient was 0.97 in previous studies (Dobson et al, 2013; Unver et al, 2015). …”
Section: Methodsmentioning
confidence: 54%
“…The chances of minimal error is quite possible with this testing procedure as variation on muscle strength does not occur drastically over days unless there is some specified neurological, metabolic or nutritional causes . Even studies on subjects with total knee replacement 30-second chair stand test showed high to very high reliability indicating the test seems to be reliable and feasible in both disease and nondisease state [12].…”
Section: Absolute Reliabilitymentioning
confidence: 99%
“…Sit-to-stand movement in nonspecific LBP Kahraman et al 167 In this study, the 30CST had very high intrarater reliability (ICC = 0.94) for patients with nonspecific LBP. The ICCs for the 30CST were between 0.84 and 0.98 in community-dwelling older adults (Jones et al, 1999), patients awaiting joint replacement surgery of the hip or knee (Gill and McBurney, 2008) and patients with total knee and hip arthroplasty (Unver et al, 2015a(Unver et al, , 2015b. These findings suggest that the 30CST is a reliable tool to assess STS movement in several conditions including nonspecific LBP.…”
Section: Discussionmentioning
confidence: 82%
“…Some previous studies indicated that the five times STS test as a field-based method has conflicting test-retest reliability results in LBP (Simmonds et al, 1998;Smeets et al, 2006). Besides this protocol, different authors have suggested several various protocols for the field-based STS test such as repeating the chair rise 10 times (Newcomer et al, 1993) and counting the number of repetitions completed during a specified time interval (either 10 or 30 s) (Bohannon et al, 1994;Thapa et al, 1994;Bohannon et al, 1995;Unver et al, 2015aUnver et al, , 2015b. Because the 30-s chair stand test (30CST) makes it possible to assess wider variations in ability levels and reduce potential floor effects (Gill and McBurney, 2008), the 30CST stands out among all of these methods.…”
Section: Introductionmentioning
confidence: 99%